Analisis Transaksi Akad Istishna dalam Praktek Jual Beli Online COD (Cash on Delivery) - Mia Septiara Siringo Ringo; Dewinta Putri Ardana; Rahman, Muhammad (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
The development of information technology has transformed trade from traditional markets to digital platforms, including Cash on Delivery (COD) payment systems. This study analyzes the integration of the COD system with the istishna contract in online transactions (specifically on Shopee), its implementation mechanisms, and its validity according to Islamic jurisprudence (fiqh muamalah). The research method used a descriptive qualitative approach through digital observation and literature review. The focus of the study was on pre-order or custom product transactions made after a specification agreement between the buyer (mustashni') and seller (shani'). The results showed that the COD system is valid in the istishna contract because it allows for final payment upon receipt of the goods. This is in accordance with Sharia law as long as the product specifications are clear, the price is transparent, and the buyer's right to khiyar is fulfilled to ensure the goods conform to the contract. As long as it is free from riba (usury), gharar (gharar), and tadlis (tadlis), the COD method in istishna transactions reflects fairness, openness, and benefits for both parties in the digital economy ecosystem.